Laparoscopic versus open resection of intrahepatic cholangiocarcinoma: nationwide analysis. Issue 4 (24th January 2021) - Hobeika, C; Cauchy, F; Fuks, D; Barbier, L; Fabre, J M; Boleslawski, E; Regimbeau, J M; Farges, O; Pruvot, F R; Pessaux, P; Salamé, E; Soubrane, O; et al.
Abstract: Background: The relevance of laparoscopic resection of intrahepatic cholangiocarcinoma (ICC) remains debated. The aim of this study was to compare laparoscopic (LLR) and open (OLR) liver resection for ICC, with specific focus on textbook outcome and lymph node dissection (LND). Methods: Patients undergoing LLR or OLR for ICC were included from two French, nationwide hepatopancreatobiliary surveys undertaken between 2000 and 2017. Patients with negative margins, and without transfusion, severe complications, prolonged hospital stay, readmission or death were considered to have a textbook outcome. Patients who achieved both a textbook outcome and LND were deemed to have an adjusted textbook outcome. OLR and LLR were compared after propensity score matching. Results: In total, 548 patients with ICC (127 LLR, 421 OLR) were included. Textbook-outcome and LND completion rates were 22.1 and 48.2 per cent respectively. LLR was independently associated with a decreased rate of LND (odds ratio 0.37, 95 per cent c.i. 0.20 to 0.69). After matching, 109 patients remained in each group. LLR was associated with a decreased rate of transfusion (7.3 versus 21.1 per cent; P = 0.001) and shorter hospital stay (median 7 versus 14 days; P = 0.001), but lower rate of LND (33.9 versus 73.4 per cent; P = 0.001). Patients who underwent LLR had lower rate of adjusted TO completion than patients who had OLR (6.5 versus 17.4 per cent; P = 0.012). Conclusion: The laparoscopic approach did not substantially improve quality of care of patients with resectable ICC. Abstract : This study assessed the oncological quality of laparoscopic liver resection for intrahepatic cholangiocarcinoma (ICC), with specific emphasis on both textbook outcome and lymphadenectomy. Although the laparoscopic approach improved the quality of surgery by reducing blood loss, transfusion rate, and hospital stay, it was nevertheless associated with a lower rate of lymphadenectomy, suggesting that this approach is currently suboptimal for ICC. Lymphadenectomy is presently acknowledged as a part of the standard treatment for ICC, and this study strongly suggests that indications for the laparoscopic approach could be extended to ICC provided that the feasibility of adequate laparoscopic lymphadenectomy is secured. Not enough adequate laparoscopic lymph node dissections